Effects of fermented banana pseudo-stem sap (Musa acuminata L.) on the growth and yield attributing characters of marigold variety Karma 555-Orange - Mehta, Aman; Rijwan Sai; Rakesh Bhujel; Navina Yadav; Sneha Khanal (Journal of Agriculture and Applied Biology, 2023)
The high cost of marigold production through the application of synthetic fertilizers and micronutrients is a major concern for Nepalese farmers. Every year, the nutrient-rich banana pseudo-stems are wasted after harvest. Utilizing the banana’s pseudo-stem for increasing marigold productivity through sustainable agricultural practices, an experiment was conducted to determine the optimum concentration of banana pseudo-stem sap (BPS) to be applied by foliar spraying to marigold variety (Karma 555 – Orange). The BPS was mixed and enriched with different ingredients, such as cow urine, cow dung, neem leaf, green gram leaf, pulse flour, vermin-liquor, jaggery, and fermented curd. The mixture was incubated under anaerobic conditions before applying the foliar spray. The study was carried out in a completely randomized block design, with three replications and seven treatments. The treatments were 0.5 % BPS, 1 % BPS, 2 % BPS, 3 % BPS, 4 % BPS, 5 % BPS, and the control. Data were recorded at 50, 70, and 90 days after transplantation (DAT). Among the treatments, the 3 % BPS solution showed significant effects on most of the growth parameters: plant height (85.07 cm), plant spread (63.47 cm) at 5% level at 90 DAT, and yield attributes such as the number of flowers per plant (74.00) at 5% level, individual flower weight (8.10 g), individual flower diameter (7.55 cm), and flower yield (597.25 g plant-1) at 1% level of significance respectively. It was found that growth and yield attributes increased with increasing concentrations of BPS up to 3 % and decreased thereafter. According to the results, foliar spray of marigold with 3 % BPS (enriched solution) resulted in the highest yield and yield components of marigold in the Chitwan area which could be an effective alternative to synthetic hormones for enhancing the growth and quality of marigolds under field conditions.